The influence of urban layout on perceived residential quality in a Costa Rican suburb - von Breymann Miranda, Helga (2024)
The chapter explores how the urban layout and residential characteristics of a Costa Rica’s suburb influence residents’ perceptions of residential quality. The study in Heredia Province also examines the effects of housing density and proximity to town centers on perceptions of residential quality. To achieve this, perceptions of residents living inside and outside housing developments (gated communities) were measured using Perceived Residential Environment Quality Indicators (PREQI). Geographic information about the study area was also collected and analyzed. Results show differences between residents living “inside” housing developments (e.g., more negatively affected by higher housing density) and those living “outside” housing developments (e.g., more negatively affected by distance to town centers). Findings support the need to attend to residential sprawl, the overdevelopment of gated communities, and the urban layout in order to ensure better residential quality in suburban developments in Costa Rica and other Latin American countries.